2023
DOI: 10.1002/hsr2.1395
|View full text |Cite
|
Sign up to set email alerts
|

The recent outbreaks of Marburg virus disease in African countries are indicating potential threat to the global public health: Future prediction from historical data

Abstract: Marburg virus disease (MVD) caused by the Marburg virus has a high mortality rate. Rousettus aegyptiacus fruit bats act as the natural reservoir host of the virus. But it can also potentially be transmitted from person to person through direct contact with body secretions. The recent outbreaks have already killed seven people out of nine confirmed cases in Equatorial Guinea and five patients out of eight confirmed cases in Tanzania. In the recent past, Ghana reported three MVD cases and two associated deaths i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The WHO and the Global Alliance for Vaccine and Immunization (GAVI) recommend 10 potential disease organisms are responsible for the disease 7 . They are Ebola, Marburg virus disease, Lassa fever, Nipah, Mers‐CoV, Zika, SARS, Cirmean‐Cong hemorrhagic fever, Rift Valley fever, and Monkeypox 8,9 . Scientists prioritize the causative organisms responsible for disease X because they spread quickly and can cause severe illness or death 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The WHO and the Global Alliance for Vaccine and Immunization (GAVI) recommend 10 potential disease organisms are responsible for the disease 7 . They are Ebola, Marburg virus disease, Lassa fever, Nipah, Mers‐CoV, Zika, SARS, Cirmean‐Cong hemorrhagic fever, Rift Valley fever, and Monkeypox 8,9 . Scientists prioritize the causative organisms responsible for disease X because they spread quickly and can cause severe illness or death 10 .…”
Section: Introductionmentioning
confidence: 99%
“…7 They are Ebola, Marburg virus disease, Lassa fever, Nipah, Mers‐CoV, Zika, SARS, Cirmean‐Cong hemorrhagic fever, Rift Valley fever, and Monkeypox. 8 , 9 Scientists prioritize the causative organisms responsible for disease X because they spread quickly and can cause severe illness or death. 10 In addition, scientists also revealed that deforestation, the wildlife trade and hunting, greater meat consumption and overuse of antibiotics in chicken farming are also factors for the above causative pathogens to cause disease X and the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the declared end, unidentified transmission chains persist, signaling a global need for vigilance in disease prevention and control. Yet, there are currently no reliable vaccines or effective treatments for this highly contagious and lethal virus [ 2 , 3 , 14 ]. Given the potential of MARV to cause large-scale outbreaks, summarizing its global research status and trends becomes pivotal.…”
Section: Introductionmentioning
confidence: 99%
“…All the probable 23 cases died later. Tanzania had recorded eight confirmed cases and five deaths till March 24, 2023 4 . One probable case also died.…”
Section: Introductionmentioning
confidence: 99%